2014
DOI: 10.1186/1743-422x-11-43
|View full text |Cite
|
Sign up to set email alerts
|

The “hidden” epidemic: a snapshot of Moroccan intravenous drug users

Abstract: BackgroundHepatitis C virus is a persistent epidemiological problem, with an estimated 170 million individuals infected worldwide, and the leading cause of asymptomatic chronic infection, liver cirrhosis and hepatocellular carcinoma. Injection drug users (IDUs) have the highest seroprevalence as compared to chronic hemodialysis and transfusion patients, and this cohort remains the most under-studied high-risk group in North Africa to date. This study first sought to characterize the demographic, epidemiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Drug addiction is a serious problem in Morocco and has been considered to be a “male-associated habit” because the overwhelming majority of drug addicts are young males who are either single or divorced. HCV seroprevalence is high among this group, reaching up to 60% [ 35 ].…”
Section: Epidemiology Of Hcv In the Maghreb Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug addiction is a serious problem in Morocco and has been considered to be a “male-associated habit” because the overwhelming majority of drug addicts are young males who are either single or divorced. HCV seroprevalence is high among this group, reaching up to 60% [ 35 ].…”
Section: Epidemiology Of Hcv In the Maghreb Regionmentioning
confidence: 99%
“…Morocco is the only country in the region that has reliable surveillance programs for HIV. Prevalence of HIV/HCV coinfections in Morocco was reported to be about 20% among injecting drug users and sex workers, but it was 10.6% among patients of different socioeconomic backgrounds [ 35 ].…”
Section: Vectors Of Hcv Transmission In the North Africamentioning
confidence: 99%
“…The average viral load for our sample was high (6log), this was expected as the majority of samples had a high viral titer upon inspection. The average viral load was not significantly higher for one genotype versus another; however, a previous study did report a significantly higher viral load for genotype 1a, and the finding might have been confirmed had the sample size been larger [Trimbitas et al, ]. Only one patient was infected with genotype 4a, while the majority of IDUs exhibit genotypes 1a and 3a.…”
Section: Discussionmentioning
confidence: 78%
“…Despite these finding, the IDU group remains one of the most poorly‐studied groups in the MENA region, with few countries having published prevalence and/or genotype data in this part of the world (Cyprus, Egypt, Iran, Israel, Lebanon, Saudi Arabia, Syria, and Morocco, respectively) [Ramia et al, ]. A recent study indicated that Moroccan drug users have a high anti‐HCV seropositivity (60%), engage heavily in needle‐sharing behaviour, and collectively exhibit genotypes 1a and 3a which differ from those found in the general population [Trimbitas et al, ]. HCV is known for its high mutations rate and confers it high genetic variability and countless subtypes [Abe et al, ; Simmonds, ].…”
Section: Introductionmentioning
confidence: 99%
“…HCV exhibits a high degree of genetic diversity ( 7 ) and is characterized by regional variations in genotype prevalence ( 8 , 9 ). It has been classified into seven genetically different genotypes, 1–7, 67 confirmed subtypes, and an additional 21 unassigned subtypes ( 10 , 11 ).…”
mentioning
confidence: 99%